Aplikasi Dialogis-Klarifikatif Apologetika Paulus Terhadap Isu Gnostisisme di Jemaat Kolose Bagi Generasi Milenial yang Terpapar Zodiak Online - Soleman Kawangmani (Institut Agama Kristen Negeri Toraja, 2020)
Abstract: The millennial generation is a generation that is familiar with the development of social media activities. This ease of access makes it to channel their hobby, one of which is accessing the horoscope (Zodiac). Christian faith must be able to provide proper clarification in the form of apologetics. The context of this problem is similar to the pattern of Paul's apologetics to the Colossians regarding the issue of Gnosticism. Based on this, the purpose of this research is: to find a pattern of apostle Paul's apology application to the contents of Gnosticism in the Colossians in the context of The millennial generation exposed by the Zodiac online. This paper uses a qualitative approach with descriptive theological and social research types. Data collection uses literature studies and interviews with millennials and God's servants who deal with zodiac addiction problems. This paper produces an apologetic pattern for millennials exposed to the Zodiac. These findings are described in 7 elements of dialogical-clarification apologetic patterns. Keywords: Millennial Generation, Zodiac, Gnosticism, Apologetics Abstrak: Generasi milenial merupakan generasi yang akrab dengan perkembangan akses media sosial. Kemudahan akses ini menjadikan untuk menyalurkan kegemaran mereka, salah satunya adalah mengakses mengenai ramalan bintang (zodiak). Iman Kristen harus dapat memberikan klarifikasi yang tepat dalam bentuk apologetika. Konteks permasalahan ini memiliki kemiripan dengan pola apologetika Paulus pada jemaat Kolose berkaitan dengan isu gnostisisme. Berdasarkan hal tersebut tujuan dari penelitian ini adalah: menemukan suatu pola penerapan apologetika rasul Paulus terhadap isi Gnostisisme di jemaat Kolose dalam konteks generasi milenial yang terpapar Zodiak online. Tulisan ini menggunakan pendekatan kualitatif dengan jenis penelitian teologis dan sosial secara deskriptif. Pengumpulan data menggunakan kajian literature dan wawancara pada generasi milenial dan hamba Tuhan yang menangani permasalahan kecanduan zodiak. Tulisan ini menghasilkan pola apologetika bagi generasi milenial yang terpapar zodiak. Temuan tersebut dideskripsikan pada 7 elemen pola apologetika dialogis-klarifikatif. Kata Kunci: Generasi Milenial, Zodiak, Gnostisisme, Apologetika